Whetstones from Viking Age Iceland: As part of the Trans-Atlantic trade in basic commodities - Juel Hansen, Sigrid Cecilie 1981- (2009)
Whetstones were essential sharpening tools from the Iron Age and well into modern times. They were an important part of people’s personal kit and indispensable to anyone using knives, axes, arrows, sickles, scythes, needles, scissors and any other iron implement or weapon with a cutting edge or point. As Viking Age Scandinavia was an Iron Age society particularly dependent on their iron tools for survival and geographic expansion stone types particularly suitable for whetting were much valued and transported over long distances. Only limited firm archaeological evidence is available to contribute to our understanding of Trans-Atlantic trade in the pre medieval period and no broad scale research has been carried out on the whetstone material in the area yet. There is no good quality stone to produce whetstones from in Iceland so almost all the material is prima facie evidence of trade and foreign connection and the fact that the trade in this commodity is well known throughout Scandinavia from the late Iron Age onwards makes it all the more promising to look at the Icelandic material. Analysis of whetstone material from nine selected farmsteads and all burials containing whetstones will be undertaken and compared to foreign reference collections in England and the Scandinavian homelands. It will primarily be the stone types used for whetting that is compared but other conditions such as the fragmentation will also be considered in order to explore Iceland’s setting in the Trans-Atlantic trade during the 9th to 12th centuries.